2022
DOI: 10.1002/1438-390x.12117
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating diapause to predict the interannual dynamics of an important agricultural pest

Abstract: We develop a new population-scale model incorporating diapause induction and termination that allows multi-year predictions of pest dynamics. In addition to predicting phenology and voltinism, the model also allows us to study the degree of overlapping among the life-stages across time; a quantity not generally predicted by previous models yet a key determinant of how frequently management must be done to maintain control. The model is a physiological, stage-structured population model that includes temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…It is also noteworthy that both cone and Circle traps succeeded in collecting post‐overwintering individuals, and cone traps proved to be particularly efficient. As such, cone traps could be used to establish a Biofix, either for the first emerging individuals or for the time they consistently emerge from diapause (Pak et al., 2022). This could then be used to construct degree‐day models to predict the future presence of GBS at particular developmental stages in the crop, as suggested for H. halys (Bergh et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is also noteworthy that both cone and Circle traps succeeded in collecting post‐overwintering individuals, and cone traps proved to be particularly efficient. As such, cone traps could be used to establish a Biofix, either for the first emerging individuals or for the time they consistently emerge from diapause (Pak et al., 2022). This could then be used to construct degree‐day models to predict the future presence of GBS at particular developmental stages in the crop, as suggested for H. halys (Bergh et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…2011). To accurately predict population dynamics, modelling could bene t by adding additional parameters that take into account diapause as it was previously developed for the codling moth (Cydia pomonella L.) (Pak et al 2022). Additionally, modelling parameters can be customized for each speci c region of the world.…”
Section: Discussionmentioning
confidence: 99%
“…The third image shows the stage-structured physiological model of Cydia pomonella. Pak et al (2022) showed that seasonal temperatures drive the survivorship, fecundity, and development rate in individuals. The authors also include diapause induction and termination, which are driven by photoperiod and temperatures, respectively.…”
Section: Cover Page Photos and Figuresmentioning
confidence: 99%
“…The authors also include diapause induction and termination, which are driven by photoperiod and temperatures, respectively. Using empirically derived laboratory data as well as a long-term time series of Cydia pomonella in the field, Pak et al (2022) fit their model and simulate the dynamics over 33 years. Because temperature ultimately drives the dynamics in Cydia pomonella, the authors simulate the model under higher temperatures to show how the dynamics, specifically its phenology, can change.…”
Section: Cover Page Photos and Figuresmentioning
confidence: 99%